2015
DOI: 10.7554/elife.08477
|View full text |Cite
|
Sign up to set email alerts
|

Central neural circuitry mediating courtship song perception in male Drosophila

Abstract: Animals use acoustic signals across a variety of social behaviors, particularly courtship. In Drosophila, song is detected by antennal mechanosensory neurons and further processed by second-order aPN1/aLN(al) neurons. However, little is known about the central pathways mediating courtship hearing. In this study, we identified a male-specific pathway for courtship hearing via third-order ventrolateral protocerebrum Projection Neuron 1 (vPN1) neurons and fourth-order pC1 neurons. Genetic inactivation of vPN1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 67 publications
4
99
2
Order By: Relevance
“…This is consistent with the results 166 of other assays that have found band-pass tuning for IPI in both sexes (Bennet-Clark and 167 Ewing, 1969;Rybak et al, 2002b;F. Von Schilcher, 1976;Zhou et al, 2015) and a sex-168 specific sign of locomotor responses (Crossley et al, 1995;F. Von Schilcher, 1976).…”
Section: Methods) 147 148supporting
confidence: 80%
See 2 more Smart Citations
“…This is consistent with the results 166 of other assays that have found band-pass tuning for IPI in both sexes (Bennet-Clark and 167 Ewing, 1969;Rybak et al, 2002b;F. Von Schilcher, 1976;Zhou et al, 2015) and a sex-168 specific sign of locomotor responses (Crossley et al, 1995;F. Von Schilcher, 1976).…”
Section: Methods) 147 148supporting
confidence: 80%
“…In the 255 central brain there are ~70 Dsx+ neurons per hemisphere in females and ~140 Dsx+ 256 neurons per hemisphere in males (Kimura et al, 2015;Rideout et al, 2010). Previous 257 studies found calcium responses to both song-like stimuli and pheromones in Dsx+ neuron 258 projections in females (Zhou et al, 2014) and tuning for the inter-pulse interval in males 259 (Zhou et al, 2015). In addition, silencing subsets of Dsx+ neurons in females affected 260 receptivity (Zhou et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The upstream neuron is then optogenetically activated while the downstream neuron expressing GCaMP6 is monitored for changes in fluorescence (Figure 6c). These experiments can be done with the nervous system kept in the body or using a dissected brain (Kallman et al 2015;Zhou et al 2015;Clowney et al 2015;Hampel et al 2015;Cohn et al 2015;Shirangi et al 2016). The functional connectivity between neurons that is demonstrated by measuring GECI responses cannot indicate whether the connections are direct, and it is always possible that intermediate neurons are involved.…”
Section: Assessing Functional Connectivity Among Neuronsmentioning
confidence: 99%
“…For example, the Drosophila JO contains about 500 mechanosensory cells, $75% of which (subgroups A, B and D) have been linked to auditory function [71], but the ascending mechanosensory pathways for conspecific song detection are likely to have substantially fewer neurons [71][72][73]. In insect auditory systems, individuali.e., unique -neurons can be identified, and in some species a single neuron alone can drive important behaviors, such as the bat-evasion reflex in noctuid moths [74].…”
Section: Curbio 13179mentioning
confidence: 99%